Studi Literatur Model Evaluasi Formatif-Sumatif Terhadap Pembelajaran Siswa Pada Mata Pelajaran IPA Di SMP Negeri 7 Muaro Jambi - rezha juniandra rezha (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2023)
In the field of education, evaluation of learning is a mandatory activity for every person who is involved in the field of education. As an educator, the learning evaluation process is useful in terms of future decision making for the progress of students in particular and the world of education in general. Formative evaluation is part of the teaching process. When incorporated into classroom practice, formative evaluation provides the information needed to adapt teaching and learning as the process occurs. In this sense, formative evaluation informs both teachers and students about a student's understanding at a point when adjustments can be made in due course. the purpose of this study is to see a description of the teacher in applying the formative-summative evaluation model in the learning process at school. This research was conducted at SMP N 7 Muaro Jambi using a qualitative descriptive method. In the end, the use of formative summative evaluation in science learning at SMPN 7 Muaro Jambi is quite effective because formative and summative evaluation is very useful for teachers and students.